The Industrial Advance Program of the Federal Reserve System - Dolley, James C. (Quarterly Journal of Economics, 1936)
Theory of the original Federal Reserve Act, 229.— Early emergency lending provisions, 231.— Emergency loan legislation, 233.— Industrial advances by the federal reserve banks, 241. —Provisions of the Act, 245.— Launching the program, 249.— Development of the program, 253.—Procedure in handling applications, 253.— Safety of loans, 256.— Profitability to the reserve banks, 263.— Necessity for the program, 264.— Reserve bank competition, 271.— Conclusions, 272.